Efetivação da educação inclusiva para estudantes com deficiência: ações-reflexões da gestão escolar - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This dissertation addresses the issue of implementing inclusive education for students with disabilities: actions-reflections of school management, a theme that is configured as a research object of the Master in Management, Education and Technologies of UEG/UnU - Luziânia. Based on this premise, the main objective is to investigate the role of the management group in the implementation of an educational process that develops inclusive practices. For this, the specific objectives are structured in: Raise the role played by the school manager group in the construction, consolidation and offer of an inclusive education for students with disabilities; Evaluate the school management plan for inclusive education for students with disabilities; Knowing the actions/attitudes, procedures, pedagogical materials and perspectives under which the inclusive education of the school unit has been proposed and implemented for students with disabilities and Analyzing how school managers make the process of inclusive education possible for students with disabilities. For the development of this work, qualitative observation, documentary research (carried out with the aim of seeking information in the documents of the Colégio Municipal Boas Novas in the city of Israelândia-GO), bibliographical research (raising published works and theoretical references by written and electronic means with related themes), descriptive research (proposing searches and describing objects/subjects in their environment) and making use of the interview in a semi-structured and objective way to the management group of the school unit, being: principal, deputy director, pedagogical coordinator and coordinator of A.E.E - Specialized Educational Assistance, aiming to gather the literature produced on the topics under discussion. At the end of this work, the concepts of school management, democratic management and inclusive education will be presented, making it possible to glimpse the role of the management group in the implementation of an educational process that develops inclusive practices in the involvement of all people, regardless of their specificities, thus circumventing the counterproductive conjectures.
Effectiveness of inclusive education for students with disabilities: actions-reflections of school management
Keywords: Escola; Gestão Escolar; Educação Inclusiva; Inclusão; Grupo Gestor; School; School management; Inclusive education; Inclusion; Managemente Group; CIENCIAS HUMANAS::EDUCACAO; EDUCACAO::ADMINISTRACAO EDUCACIONAL; TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL